2016
DOI: 10.1037/law0000078
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the stability of psychopathy scores in adolescents versus adults: How often is “fledgling psychopathy” misdiagnosed?

Abstract: Can psychopathy be identified as accurately during adolescence as adulthood? To address this developmental question, this study compared the stability of scores on the leading measure of psychopathy, the Psychopathy Checklist (PCL), among 202 adolescent (M ϭ 15.8 years, SD ϭ 0.89) and 134 adult (M ϭ 27.5, SD ϭ 1.08) offenders. Over a 2-year period, adolescents' total scores on the PCL (r ϭ .33) were less stable than those of adults (r ϭ .71). Adolescents' baseline PCL scores also weakly predicted psychopathy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 98 publications
1
26
0
1
Order By: Relevance
“…Although psychopathy is associated with higher offending frequencies (Dyck et al, 2013) and variance between CMS and single style offenders was found for the duration of the present study, CMS offenders did not report significantly different levels of psychopathic traits at any point in the regression analyses. The discrepancy can be explained by the dynamic nature of psychopathy during adolescence (Cauffman et al, 2016) and may also represent variation of offending style for individuals with higher psychopathic traits. The only psychological risk factor where CMS offenders reported significantly higher levels was impulse control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although psychopathy is associated with higher offending frequencies (Dyck et al, 2013) and variance between CMS and single style offenders was found for the duration of the present study, CMS offenders did not report significantly different levels of psychopathic traits at any point in the regression analyses. The discrepancy can be explained by the dynamic nature of psychopathy during adolescence (Cauffman et al, 2016) and may also represent variation of offending style for individuals with higher psychopathic traits. The only psychological risk factor where CMS offenders reported significantly higher levels was impulse control.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal research has shown that solo‐offenders display fewer psychopathic traits than co and mixed style offenders as they age (Goldweber et al, 2011). Also relevant is research that has found psychopathic traits to be a dynamic risk factor for adolescents (Cauffman, Skeem, Dmitrieva, & Cavanagh, 2016). Researchers found a correlation between higher psychopathic levels and offending frequencies in a sample of adolescent offenders (Dyck, Campbell, Schmidt, & Wershler, 2013); however, they also demonstrated that offending frequencies for this group decreased with age.…”
Section: Social and Psychological Risks Factorsmentioning
confidence: 99%
“…Although proactive aggressive behaviors may predict elevated psychopathy in adulthood, it is not conclusive, and factors such as maturity may affect adolescent followup scores (Cauffman, Skeem, Dmitrieva, & Cavanagh, 2016), perhaps because of the increasing maturity of the prefrontal cortex during adolescence and the gradual regulation of impulsive aggression (Fung et al, 2009), and the deficiencies in empathic cognitive and affective capacity reported by people with high levels of PA and RA (Euler, Steinlin, & Stadler, 2017). These obvious differences in the indicators of invariance represent new lines of research of the RPQ in female samples and adults over 25 years of age, as stated by Raine et al (2006), when reporting inconsistencies in the generalization for these population groups, according to the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although proactive aggressive behaviors may predict elevated psychopathy in adulthood, it is not conclusive, and factors such as maturity may affect adolescent follow-up scores ( Cauffman, Skeem, Dmitrieva, & Cavanagh, 2016 ), perhaps because of the increasing maturity of the prefrontal cortex during adolescence and the gradual regulation of impulsive aggression ( Fung et al, 2009 ), and the deficiencies in empathic cognitive and affective capacity reported by people with high levels of PA and RA ( Euler, Steinlin, & Stadler, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…É sabido que o uso de pontos de corte para a identificação de psicopatia tem sido inconsistente mesmo em adultos (Cauffman, Skeem, Dmitrieva, & Cavanagh, 2016;Marcus, 2017). Por exemplo, Walters, Ermer, Knight e Kiehl (2015) avaliaram 445 detentos de instituições de segurança máxima, que participaram de um estudo que utilizou medidas de traços psicopáticos e ressonância magnética estrutural para avaliar indicadores de concentração de substância cinzenta (GMC, nos participantes adultos) e de volume de substância cinzenta (GMV, em participantes adolescentes).…”
Section: Considerações Finaisunclassified